Matrix Metalloproteinases 9 Expresion of Thyroid Follicular Neoplasm FNAB and Its Relationship with Thyroid Malignancy Histopathology - Oktora, Meta Zulyati; Harahap, Wirsma Arif; Agus, Salmiah (Majalah Patologi Indonesia, 2024)
Background Fine-Needle Aspiration Biopsy (FNAB) thyroid nodules is not easy to distinguish betwen follicular malignancy and follicular benign lession. Malignancy diagnosis can only be made from histopathology examination by examing tumor invation to capsule and vaskular. Matrix Metalloproteinase 9 (MMP-9) examination can be added to help making initial diagnois. MMP-9 is a proteolytic enzyme that plays important role in cancer progressivity, especially in thyroid. High MMP-9 expression will lead to earlier degradation of thyroid and its will make the cell metastasist easier. This study is to examine MMP-9 expression of thyroid follicular neoplasm related tomalignancy through histopathology examination and the diagnostic test of FNAB MMP-9 expression and histophatologic examination. Methods We used 42 sample FNAB follicular thyroid in Anatomic Pathology laboratories RSUP M Djamil Padang and histopathologic examination was performed. Immunohistochemical was staining with primary antibody MMP-9 then its expression were assessed in stroma and cytoplasmic cell tumour. Results MMP-9 expression was found positive in malignancy histopathologic (80.9%). Expression of MMP-9 at FNAB folikullar neoplasm thyroid is significant in malignant histopathologic thyroid (p=0.017). MMP-9 Sensitivity in thyroid follicular noduleFNAB is quite good (88.575) and its specificity is 51.14%. Conclusion Increased MMP-9 expression of FNAB follicular thyroid neoplasm is associated with histopathologic malignancy.